CAN IMPARED SYSTOLIC FUNCTION BE DETECTED FROM PRESSURE WAVEFORMS?. (June 2022) - Orter, Stefan; Hametner, Bernhard; Wassertheurer, Siegfried; Danninger, Kathrin; Argyris, Antonis; Protogerou, Athanase; Kaniusas, Eugenijus; Binder, Ronald; Weber, Thomas
Abstract : Objective: Heart failure with reduced ejection fraction (HFrEF) is a significant health problem. Early diagnosis, using widely available, cheap methods, remains an important goal. Therefore, we investigated whether individuals with normal left ventricular ejection fraction (EF) can be discriminated from patients with reduced EF with contemporary, automated analysis of pressure pulse waveforms. Design and method: Left ventricular EF was measured prospectively in 78 patients with HFrEF (15 females) with echocardiography (apical 4 chamber view, Simpson`s method, on a Philips EPIQ system). The control group was matched for age, sex, height, weight, and brachial blood pressure. Pressure waveforms were acquired from the radial artery (SphygmoCor system, AtCor medical) and processed with ARCSolver algorithms to derive Wave Intensity Analysis (WIA) parameters S and D and their ratio (SDR). Additionally, left ventricular ejection time index (iLVET) was calculated using a method based on numerical derivatives. Clinical characteristics between patients and controls were compared, using t-tests or Mann Whitney U test, as appropriate. Receiver-operating-curves (ROC) analysis was performed to investigate the discriminative ability of the pulse waveform parameters. Results: Patients with HFrEF (mean EF░=░28%) and controls (mean EF░=░66%) were well matched, according to age (56 vs. 56░years, p░=░0.597), sex, height (1.74 vs. 1.73 m, p░=░0.576), weight (86 vs. 83░kg, p░=░0.590), brachial systolic (127 vs. 129░mmHg, p░=░0.359) and diastolic (79 vs.79░mmHg, p░=░0.763) blood pressure, and the presence of hypertension (51 vs. 51%) respectively. Mean heart rate of patients and controls differed slightly (65 vs. 61 BPM, p░=░0.040). Diabetes, coronary artery disease, and the use of ACE-inhibitors/Angiotensin Receptor Blockers/Angiotensin Receptor Neprilysin Inhibitors were more prevalent in patients, as compared to controls. SDR (2.4 vs. 5.7 %, p░<░0.001) and iLVET (0.39 vs. 0.42, p░<░0.001) were significantly lower in HFrEF patients, as compared to controls. Moreover, SDR (AUC░=░0.93, 95% CI░=░[0.96, 0.88]) and iLVET (AUC░=░0.90, 95% CI░=░[0.94, 0.83]) were highly discriminative between HFrEF patients and controls – fx30. Conclusions: Parameters derived from pressure pulse waveforms, obtained non-invasively and processed automatically, may be suitable for early diagnosis of severely impaired EF.